From an Anthropological perspective to the elaboration of a knowledge management system in West Africa - (:unkn) unknown (My University, 2016)
As the mutation of Humanities and Social Science supported by the disruption of information science paradigms and communication, knowledge organization systems to those worn by knowledge societies, it‟s important to reconsider the relationship between individuals, communities and technology in a learning process environment for knowledge capitalization. The objective of this thesis is to propose a hybrid model of knowledge capitalization supported by knowledge management in Benin context.The aims of this proposal, is to improve the results of the re-use of business knowledge. So we will start with a questioning of the existence of an endogenous knowledge capitalization model which can boost the development of West African enterprises in general and Benin in particular.To verify the possibility of the application or transposition of this traditional model to the realities of the business, we focuse on the factors that may affect the efficiency of the transfer process for capitalization. These factors were identified in our literature review in which we found multitude of techniques and theoretical approaches to understand the phenomenon. However, in this research, we are divided between two dominant schools of thought in this subject area that are constructivism and positivism. In this momentum, we start from an anthropological perspective towards the establishment of a knowledge capitalization system in West Africa. Inspired by the way the Yoruba Nago communities and Fa perceive corporate life and the transmission of knowledge (what knowledge transferred, for which tools and the impact of this transfer on the community).To achieve this goal mention above, we will conduct a qualitative exploratory approach to the various players in the Fa community of practice and also in some enterprises in Benin. This through the implementation (adaptation) of a knowledge capitalization device in the company, taking into account cultural and anthropological realitie
Keywords: African Research